Saúde e cogestão popular: os limites e desafios da implantação e efetivação dos conselhos locais de saúde em um território da cidade de Santos/SP - Benedito, Ivone Leal [UNIFESP] (2014)
The present study aimed to investigate the development, operation and impact of Conselhos Locais de Saúde (CLS) in the co-management of primary care of the Sistema Único de Saúde (SUS) of Santos / SP from a specific territory, which was the region of Morros. The methodological path followed was the qualitative approach, carrying out field research to collect primary source. During the exploratory phase visits in locus were conducted in seven of eight primary care units belonging to the territory searched.These visits were analyzed all the minutes of the Board since their election. It was also made visits to the Conselho Municipal de Saúde de Santos (CMS) in order to understand and know about the process of implementation and monitoring of these CLS. To support this research semi-structured interviews were conducted with the directors (manager / user / professional area), as well as professionals and users who are not as representatives of the Local Council of the same units. Found on analysis that arise from the Local Councils intention of encouraging closer relations between primary care units with the local community. The CLS was created by resolution of CMS in 2006, but only in 2008 the municipal administration chose to start the implementation process into three units healths with one primary care unit located on the territory searched. After two years of experience, CMS opened the electoral process in other primary care units in the city. In the region of hills, elections were held between October 2010 to September 2011, lasting almost a year. In this period, since the elections, we observe that these CLS suffered decline in the frequency of meetings and solidification of CLS. However, we identify as potential local comanagement enriching experiences to think about participation, social control and local health policy. But although they have lived these experiences, the CLS still cannot play a role of co-management in health policy and those involved are very fragile in the public participation process. Much disinformation and poor coordination between the actors and agencies involved in the process of social control has been found. The CLS are privileged to units and territories spaces but require reflection and encouragement in political education by all stakeholders: local and municipal government; directors of CLS; CMS; health professionals and the SUS.